RELATIONSHIP OF BLOOD MUSCLE EXPLOSION POWER TO THE ABILITY OF RUNNING AWAY AT AIR WALKING STYLE IN XSMA HOSANA CLASS STUDENTS - Siregar, Fajar Sidik (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna Medan, 2020)
A long jump is a form of jumping motion lifting the leg up forward in an effort to bring the weight point as long as possible in the air which is done with the repulsion of one leg to reach the greatest distance. The object and pedestal of the long jump are to achieve the greatest possible distance of the jump. The distance of the jump is measured from the repulsion board to the nearest limit of the landing position produced by the body part. The purpose of this study was to determine the relationship between leg power and the long jump ability of HosanaMedan high school students. Based on the results of data processing, it can be concluded that there is a positive and significant relationship between the explosive power of the leg muscles on the long jump ability (r = 0.72), the explosive power of the leg muscles contributes 51.84% to the long jump ability of Class X students of SMA Hosana Field.